2009
DOI: 10.1063/1.3086935
|View full text |Cite
|
Sign up to set email alerts
|

Probing the geometry dependence of molecular dimers with two-dimensional-vibronic spectroscopy

Abstract: Two-dimensional (2D) vibronic correlation spectra of molecular dimers are calculated, taking a single vibration in each monomer into account. Within the employed wave function approach, the coupling to a surrounding is included only phenomenologically. It is shown that this offers a straightforward understanding of the spectra. The influence of the relative orientation of the monomer transition dipole moments and the electronic coupling strength is investigated. Employing a model for perylene bisimide, we pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…16 There have been considerable theoretical efforts to elucidate the role of vibrational DOF in the dynamics of charge and exciton transport. 1,3,16,17,[19][20][21][22][23][24][25][26] It has been shown that explicitly accounting for effective vibrational DOFs (vibronic model) rather than incorporating them into the thermal reservoir (electronic model) can predict the system dynamics in better agreement with the experiment. 1,17, 23 Christensson et al 1 predicted the long-lived oscillations in the 2D spectra of the FMO complex with dephasing times that agree with the experimental results using a vibronic model, whereas the electronic model predicts a much faster time scale by an order of magnitude.…”
Section: Introductionmentioning
confidence: 76%
“…16 There have been considerable theoretical efforts to elucidate the role of vibrational DOF in the dynamics of charge and exciton transport. 1,3,16,17,[19][20][21][22][23][24][25][26] It has been shown that explicitly accounting for effective vibrational DOFs (vibronic model) rather than incorporating them into the thermal reservoir (electronic model) can predict the system dynamics in better agreement with the experiment. 1,17, 23 Christensson et al 1 predicted the long-lived oscillations in the 2D spectra of the FMO complex with dephasing times that agree with the experimental results using a vibronic model, whereas the electronic model predicts a much faster time scale by an order of magnitude.…”
Section: Introductionmentioning
confidence: 76%
“…On the other hand, recent simulations have revealed unexpected effects on the electronic structure and dynamics if vibrational modes are explicitly included in the system. 2224 Motivated by these results, we apply a vibronic exciton Hamiltonian in the one particle approximation 2527 to FMO, in which one vibrational mode on each monomer is treated explicitly. Including significant vibrational modes explicitly into system enables us to avoid approximations which would otherwise arise from their perturbative treatment as members of the bath.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained time-signal resembles the form of (15) with complex-conjugate exponential term and a dipole correlation function (analogical to (11) containing the R 1 , R 4 correlation functions [3] and an additional 2E part). In order to show the possibility of obtaining analytic FT of PE signals, in what follows we disregard non-rephasing contribution [10].…”
Section: Methodsmentioning
confidence: 99%
“…Application of this approach to electronically coupled dimers partially resembles the wavefunction description by Seibt et al, [10], where local vibrations and finite pulse width of exciting pulses are included and to some extend also to the doorway-window approach [11]. Our aim is to derive analytical results for 2D-PE FT signals for a complex, finite state electronic system no matter of the importance of vibronic spectra [10].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation